2020
DOI: 10.1167/iovs.61.11.21
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Promotes Cellular Senescence in Exchange for Blocking Subretinal Fibrosis in Age-Related Macular Degeneration

Abstract: Purpose To determine whether caveolin-1 (i) prevents epithelial–mesenchymal transition in the RPE and laser-induced subretinal fibrosis and (ii) promotes or inhibits cellular senescence in the RPE. Methods We examined laser-induced subretinal fibrosis and RPE cell contraction in wild-type and Caveolin-1 knockout ( Cav-1 −/− ) mice treated with or without cavtratin, a cell-permeable peptide of caveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…No claim to completeness. CNV: choroidal neovascularization, OIR: oxygen induced retinopathy, RPE: retinal pigment epithelium Therapy Model Route of administration Reference Ac-EEED (actin blockage) Mouse, laser CNV intravitreal Caballero et al ( 2011 ) Adrenomedullin Mouse laser CNV intravitreal Tanaka et al ( 2020 ) Cavtratin (caveolin-1) Mouse laser CNV intravitreal Shimizu et al ( 2020 ) Connective tissue growth factor antagonism Rat laser CNV intravitreal Daftarian et al ( 2019 ) Cyclooxygenase 2 antagonism (NS-398) Mouse laser CNV intraperitoneal Zhang et al ( 2016 ) Doxycyclin Mouse laser CNV intraperitoneal Peng et al ( 2018 ) Fibroblast growth factor 2 antagonism (RBM-007) Mouse and rat laser CNV intravitreal Matsuda et al ( 2019 ) Heat shock protein 70 Mouse subretinal fibrosis intravitreal Yang et al ( 2013 ) Interleukin 6 antagonism Mouse subretinal fibrosis intravitreal Sato et al ( 2018b ) Interleukin 6 receptor antagonism Mouse subretinal fibrosis intravitreal Sato et al ( …”
Section: Growth Factorsmentioning
confidence: 99%
“…No claim to completeness. CNV: choroidal neovascularization, OIR: oxygen induced retinopathy, RPE: retinal pigment epithelium Therapy Model Route of administration Reference Ac-EEED (actin blockage) Mouse, laser CNV intravitreal Caballero et al ( 2011 ) Adrenomedullin Mouse laser CNV intravitreal Tanaka et al ( 2020 ) Cavtratin (caveolin-1) Mouse laser CNV intravitreal Shimizu et al ( 2020 ) Connective tissue growth factor antagonism Rat laser CNV intravitreal Daftarian et al ( 2019 ) Cyclooxygenase 2 antagonism (NS-398) Mouse laser CNV intraperitoneal Zhang et al ( 2016 ) Doxycyclin Mouse laser CNV intraperitoneal Peng et al ( 2018 ) Fibroblast growth factor 2 antagonism (RBM-007) Mouse and rat laser CNV intravitreal Matsuda et al ( 2019 ) Heat shock protein 70 Mouse subretinal fibrosis intravitreal Yang et al ( 2013 ) Interleukin 6 antagonism Mouse subretinal fibrosis intravitreal Sato et al ( 2018b ) Interleukin 6 receptor antagonism Mouse subretinal fibrosis intravitreal Sato et al ( …”
Section: Growth Factorsmentioning
confidence: 99%
“…Several studies explained that anti-VEGFA treatment promoted the formation of fibrotic scars in the subretinal space, and fibrotic changes could reduce the efficacy of the anti-VEGFA pathway [6][7][8]. Therefore, the treatment of progressive fibrosis, including the reversal of EMT and the restoration of the epithelial phenotype, should be potential targets for neovascular AMD-related subretinal fibrosis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…29 Key components of the inflammatory process in uveitis include the invasion of the eye by both T cells and macrophages, breakdown of the blood-retinal barrier, edema, and leakage of protein into the aqueous and vitreous. Prior work has shown that AP-Cav reduced the influx of inflammatory cells in an immune models of MS, asthma, and retinal disease [17][18][19]28 and reduced the actions and production of cytokines. 15,30 Therefore, we examined the actions of CVX51401 in the IRBP model of uveitis that has a strong immunological and cytokine component to disease pathogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…It would be of interest to test CVX51401 in models of retinal and choroidal leakage and neovascularization because AP-Cav was additive with an anti-VEGF antibody in reducing retinal disease and more recently shown to reduce epithelial-mesenchymal transition and laser induced subretinal fibrosis. 28 Uveitis is a collection of conditions causing inflammation of the uveal tract (iris, ciliary body, and choroid) and often involves the retina. Current treatment goals are the suppression of inflammation using steroids in combination with immunomodulators such as methotrexate, mycophenolate mofetil, and biologic modifiers in combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation